DEVELOPMENT IN THE MANAGEMENT OF SOCIOECONOMIC SYSTEMS - S. Zainullin; N. Sorokin (Вестник университета)
The article presents a brief analysis of the development strategy of the socio-economic system on the example of PJSC Sollers. This company is the largest manufacturer of automotive vehicles. In this regard, first of all, it should be noted features of its business model, which provides a strategy for the formation of strong competitive advantages in the industry market. The development of the company is provided by a high level of manufacturability, which is in priority. This ensures that the company can be included in the value chain of the strongest global automotive brands. The article also pays attention to the presence of a mature positive corporate culture, which the company managed to form, despite the complex holding structure of management.